2017
DOI: 10.1158/2326-6066.cir-16-0223
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Melanoma Patient Had a Complete Response with Clonal Expansion after Whole Brain Radiation and PD-1 Blockade

Abstract: We report here on a patient with metastatic melanoma who had extensive brain metastases. After being treated with the sequential combination of whole brain radiation therapy followed by the PD-1-inhibitory antibody, pembrolizumab, the patient had a durable complete response. Retrospective laboratory studies of T cells revealed that, after treatment with anti-PD-1 commenced, effector CD8 T cells in the blood expanded and the ratio of CD8:Treg T cells increased. A CD8 T-cell clone present in the initial brain me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…The same T cell clone was found in peripheral blood at the frequency of 6.1% before the treatment and was expanded to 21.0% at week 10. This frequency is similar to that reported in a melanoma patient who showed complete radiological response [20], thus monitoring T cell clonal dynamics using this comprehensive approach (i.e. analyses of entire repertoire) may reflect response to therapy more accurately.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The same T cell clone was found in peripheral blood at the frequency of 6.1% before the treatment and was expanded to 21.0% at week 10. This frequency is similar to that reported in a melanoma patient who showed complete radiological response [20], thus monitoring T cell clonal dynamics using this comprehensive approach (i.e. analyses of entire repertoire) may reflect response to therapy more accurately.…”
Section: Discussionsupporting
confidence: 83%
“…The assessment of these processes at clonal levels of T cells has recently been achieved by advances in high-throughput sequencing technologies [16,17], which have enabled us to identify millions of individual TCR sequences and provide the opportunity to track each of them longitudinally. Previous analyses of samples at two time-points (before and after the treatment) in a small cohort of patients revealed correlation between clonal expansion of certain T cells and clinical responses to immune checkpoint blockades [18][19][20]. Such findings are consistent with other reports which suggested of the patient.…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, we showed that the T‐cell receptor (TCR) repertoire of tumor‐infiltrated T cells might be useful information for the evaluation or assessment of the immune microenvironment . Recent reports, including ours, suggested that durable response to immune checkpoint blockade correlated with early and sustained expansion of a few dominant T‐cell clones in peripheral blood, and that TCR sequencing can be used to detect early signs of response/resistance to immune checkpoint blockade …”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 81%
“…8 Recent reports, including ours, suggested that durable response to immune checkpoint blockade correlated with early and sustained expansion of a few dominant T-cell clones in peripheral blood, and that TCR sequencing can be used to detect early signs of response/resistance to immune checkpoint blockade. 11,12 A series of studies have also addressed the relationship between mutational burden and immunotherapeutic outcome. Early studies supported the hypothesis that the extent of DNA damage is correlated with therapeutic response in melanoma patients treated with anti-CTLA-4 antibody, 13 and non-small-cell lung cancer patients treated with anti-PD1 antibody.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Systemic tumor control via the immune system can be triggered by radiation-induced changes to the tumor microenvironment as well as surrounding stromal cells [11]. The potent effects of this treatment combination have been observed in experimental studies [15,16] as well as several clinical studies for different cancer types such as brain metastases [17], head and neck squamous cell carcinoma [18], metastatic pancreatic cancer [19], lung cancer [20], and metastatic melanoma [21]. The discovery of immune checkpoint inhibitors (ICI) has led to significant advancements in immunotherapy.…”
Section: Introductionmentioning
confidence: 99%